Акумуляція деяких важких металів тополями та особливості міграції елементів у системі “ґрунт–рослина” - Gryshko, V.N.; Danilchuk, А.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
We are studied dependence between maintenance of heavy metals in soil on the industrial grounds of ore mining enterprises of Kryvorozh'ya and their accumulation in leaves, petioles, buds and wood of one-year shoots of Populus deltoides Marsh., P. italica Moench, P. simonii Carr., P. candicans Ait. and P. bolleana L. It was determined speciesspecificity in accumulation of Fe, Zn, Ni, Cu, Pb and Cd, confirmed with the indexes of intratissue contamination of poplars. It has been established the coefficients of accumulation and redistribution of heavy metals in the "soil – plants" system.